Transformasi Digital Kampung Wisata Gatot sebagai Niche Market Gastronomi Tradisional - Adrian Hartanto Darma Sanputra; Evi Fitriana; Apriana Rahmawati; Ghina Mufidatus Salma; Ervina Dwi Aprilia (Indonesian Journal of Society Engagement, 2025)
This community service program aims to transform Kampung Wisata Gatot Sumberpucung into a traditional gastronomy niche market destination through the Strategy-Action-Technology (S.A.T) approach. The implementation method uses participatory action research involving 25 Pokdarwis members and 15 MSME actors. Activities were carried out for 8 months through a series of workshops, training, and cultural festivals. The program results showed an increase in gatot production capacity from 50kg to 150kg per month, implementation of PIRT standard hygienic SOPs, digitalization of bookkeeping systems, development of integrated digital marketing platforms, and organizing the Kampung Gatot Festival which successfully attracted 500 visitors. This program successfully transformed Kampung Gatot into a gastronomic tourism destination that combines local wisdom with digital technology. The economic impact can be seen from the 30% increase in MSME income and the creation of 10 new jobs. This program supports the achievement of SDGs point 8 on decent work and economic growth and point 11 on sustainable communities. Program sustainability is guaranteed through the formation of an independent management team and commitment to allocate 10% of profits for community development. Abstrak Program pengabdian kepada masyarakat ini bertujuan mentransformasi Kampung Wisata Gatot Sumberpucung menjadi destinasi niche market gastronomi tradisional melalui pendekatan Strategy-Action-Technology (S.A.T). Metode pelaksanaan menggunakan participatory action research dengan melibatkan 25 anggota Pokdarwis dan 15 pelaku UMKM. Kegiatan dilaksanakan selama 8 bulan melalui serangkaian workshop, pelatihan, dan festival budaya. Hasil program menunjukkan peningkatan kapasitas produksi gatot dari 50kg menjadi 150kg per bulan, implementasi SOP higienis standar PIRT, digitalisasi sistem pembukuan, pengembangan platform pemasaran digital terintegrasi, serta penyelenggaraan Kampung Gatot Festival yang berhasil menarik 500 pengunjung. Program ini berhasil mentransformasi Kampung Gatot menjadi destinasi wisata gastronomi yang menggabungkan kearifan lokal dengan teknologi digital. Dampak ekonomi terlihat dari peningkatan pendapatan UMKM sebesar 30% dan terciptanya 10 lapangan kerja baru. Program ini mendukung pencapaian SDGs poin 8 tentang pekerjaan layak dan pertumbuhan ekonomi serta poin 11 tentang komunitas berkelanjutan. Keberlanjutan program dijamin melalui pembentukan tim pengelola mandiri dan komitmen alokasi 10% keuntungan untuk pengembangan komunitas. Kata Kunci: ceruk pasar; gastronomi tradisional; transformasi digital; kampung wisata; pemberdayaan masyarakat